Association between dietary intake of protein and amino acids and sarcopenia: a cross-sectional study - Weixia Yuan; Panpan Ao; Yun Ma; Ying Ma; Juan Song; Shaofeng Wei; Lijia Yuan (PLoS ONE, 2025)
Objective To research the effects of diet on sarcopenia, and to examine the association of protein and amino acid sources with the risk of sarcopenia in older adults. Methods From December 2023 to July 2024, 84 patients with sarcopenia and 173 without sarcopenia were included in the study at the Joint Logistics Support Force 925th Hospital. We compared the in diet and general characteristics between the two groups. Multivariate logistic regression analysis was performed to assess the effects of total protein, animal protein, plant protein, and amino acid on the risk of sarcopenia in older adults. Results In terms of nutrient intake, the dietary intakes of energy, protein, fat, carbohydrates, and dietary fiber were significantly lower in the sarcopenia group than the non-sarcopenia group (P < 0.05). Analysis of protein showed that the highest tertile of total protein and animal protein intake was associated with lower incident sarcopenia risk (P < 0.05), while plant protein intake showed no significant association. Further analysis of amino acid showed that the highest tertile of leucine, glutamate, cystine, and tyrosine intake was associated with increased risk of sarcopenia, whereas arginine intake was linked to a lower incident sarcopenia risk (OR: 0.442, 95% CI: 0.200 ~ 0.979; P-trend = 0.038). Conclusions The insufficient intake of animal protein and amino acids may be closely associated with the risk of sarcopenia in older adults. Moderately increasing the intake of arginine and animal protein may help reduce the risk of sarcopenia in older adults.